EVALUASI PERATURAN BUPATI INDRAGIRI HULU NOMOR 74 TAHUN 2011 TENTANG IZIN PENANGKARAN SARANG BURUNG WALET - Delismayani Hasibuan; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indragiri Hulu Regent Regulation No. 74 in 2011 About the breeding Permit the bird nestSwiftlet is one of the policies made by the Government of Indragiri Hulu Regency to govern andregulate the swiftlet bird nest penangkar's relic in Indragiri Hulu Regency. This rule was madeto follow where this regulation aims to Swiftlet breeding entrepreneurs doing business inaccordance with the provisions and rules that have been created, and by the presence of thepenangkar of these regulations are required to have permission of the swiftlet breeding ventureowned.This research aims to analyze and evaluate the Indragiri Hulu Regent Regulation No. 74in 2011 About bird's nest Swiftlet Breeding Permissions and knowing the impact that any ofthese regulations. This research was conducted in Indragiri Hulu Regency, using qualitative,descriptive methods with techniques of collecting data through observation and interviews withparties – parties involved in Regulation of Indragiri Hulu Regent No. 74 in 2011 About thebreeding Permit this Swiftlet bird nest. This research was conducted by using the theory ofPolicy Evaluation according to William N. Dunn.The results of this research show that has not yet been effectively demonstrated by thisregulation has not been accomplished the purpose of these regulations such as creating publicorder of society and an increase in Income to the Original Area. This policy has been in force forthree years but has yet to get the desired results. No successful regulation to achieve the goaldue to the effectiveness of regulation which has not been able to achieve the expected goal, lesseficient this rule that is caused due to the lack of coordination between the technical teamImplementing the policy, specifically due to lack of Government Regulation, as well as inrunning the responsiveness of policy objectives targets very low or do not care about the rulesapply.Keywords: Public Policy, Policy Formulation, and Evaluatio